Konseling Kelompok Social Cognitive Career Therapy dalam Pengambilan Keputusan Karir - Himsonadi, Himsonadi; Majdi, M. Zuhdi Zainul (MODELING: Jurnal Program Studi PGMI, 2024)
The purpose of this study was to determine the effectiveness of social cognitive career therapy group counseling in student career decision making. This study used a repetitive measure experimental design with pretest and multiple posttest designs. The subjects in this study were 6 students at the Hamzanwadi Pancor Islamic Institute. 3 male students and 3 female students were selected using a purposive sampling technique. Data collection used the career decision making self efficacy short form scale instrument. Data analysis using repeated measure ANAVA. The results of this study indicate that social cognitive career therapy group counseling is effective in improving student career decision making at the Hamzanwadi Pancor Islamic Institute. In addition, female students have a higher level of career decision making than male students. Abstrak Tujuan dari penelitian ini adalah untuk mengetahui kefektifan dari konseling kelompok social cognitive career therapy dalam pengambilan keputusan karir mahasiswa. Penelitian ini menggunakan rancangan eksperimen repetead measure dengan pretest and multiple posttest design. Subjek dalam penelitian ini sebanyak 6 orang mahasiswa di Institut Agama Islam Hamzanwadi Pancor. 3 mahasiswa laki-laki dan 3 mahasiswa perempuan yang diseleksi menggunakan teknik purposive sampling. Pengumpulan data menggunakan instrumen the career decision making self efficacy short form scale. Analisis data menggunakan repeated measure ANAVA. Hasil dari penelitian ini menunjukkan bahwa konseling kelompok social cognitive career therapy efektif di dalam meningkatkan pengambilan keputusan karir mahasiswa di Institut Agama Islam Hamzanwadi Pancor. Selain itu mahasiswa perempuan lebih tinggi tingkat pengambilan keputusan karirnya dibandingkan dengan mahasiswa laki-laki.